2017
DOI: 10.1128/mbio.00893-17
|View full text |Cite
|
Sign up to set email alerts
|

Deep-Sea Hydrothermal Vent Viruses Compensate for Microbial Metabolism in Virus-Host Interactions

Abstract: Viruses are believed to be responsible for the mortality of host organisms. However, some recent investigations reveal that viruses may be essential for host survival. To date, it remains unclear whether viruses are beneficial or harmful to their hosts. To reveal the roles of viruses in the virus-host interactions, viromes and microbiomes of sediment samples from three deep-sea hydrothermal vents were explored in this study. To exclude the influence of exogenous DNAs on viromes, the virus particles were purifi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
63
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 70 publications
(64 citation statements)
references
References 53 publications
0
63
0
1
Order By: Relevance
“…AMGs have been previously described for several enzymes involved in the biochemical cycles for most of the major elements comprising life including C, P, and S [23,[60][61][62]. Notably missing from this list were prominent N-related AMGs, but the discovery the nitrogen regulators ntcA in cyanophage [63]; P II and ammonia transporters (amt) on viral contigs [21]; amoC AMGs (in [21] and here); and more recently nitrate reductase genes in deep-sea vent viromes [64], have expanded the known set of key biogeochemical pathways impacted by viral AMGs. Viral infection should generally limit the abundance and thus contribution of Thaumarchaeota to nitrification, but cells infected by amoC-carrying viruses presumably still can contribute to nitrification.…”
Section: Tablementioning
confidence: 98%
“…AMGs have been previously described for several enzymes involved in the biochemical cycles for most of the major elements comprising life including C, P, and S [23,[60][61][62]. Notably missing from this list were prominent N-related AMGs, but the discovery the nitrogen regulators ntcA in cyanophage [63]; P II and ammonia transporters (amt) on viral contigs [21]; amoC AMGs (in [21] and here); and more recently nitrate reductase genes in deep-sea vent viromes [64], have expanded the known set of key biogeochemical pathways impacted by viral AMGs. Viral infection should generally limit the abundance and thus contribution of Thaumarchaeota to nitrification, but cells infected by amoC-carrying viruses presumably still can contribute to nitrification.…”
Section: Tablementioning
confidence: 98%
“…Previous work has suggested that viruses in hydrothermal systems have the genomic 561 capacity to alter their hosts' microbial metabolism through harboring auxiliary metabolic genes 562 (AMGs) [17][18][19]. We found a higher percentage of microbial genomes with putative viral 563 sequences (40%) than has been previously reported for single-cell genomes (SAGs, 10%) in 564 diffuse flow hydrothermal fluids [15].…”
mentioning
confidence: 64%
“…[14,15]. In addition to acting as microbial predators, phages might confer an enhanced level of fitness to the microbial host, enhancing host survival in the extreme environment [16]. In the strain SY095 genome, four putative prophages were identified, named CTV1 to CTV4.…”
Section: Data Descriptionmentioning
confidence: 99%